2019
DOI: 10.1515/mammalia-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Sympatry and habitat associations of sigmodontine rodents in a neotropical forest-savanna interface

Abstract: Small mammal communities in the Neotropics are composed largely of sigmodontine rodents. However, many questions regarding these communities remain unanswered, especially those pertaining to fine-scale sympatry and habitat selection. To address this, we examined sigmodontine community structure and vegetation in the western margin of the Upper Paraná Atlantic Forest and the southwestern-most extent of the Cerrado (CE) (an extensive South American savanna ecoregion) of Paraguay. Vegetation classifications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…However, further analysis of station-level vegetation measurements revealed that each grid was heterogeneous ( Figure 4 ; Figure S1 ). As the data suggested that the distribution of these rodents was associated with fine-scale “microhabitat” characteristics ( Table S3 ) [ 36 ], we were interested in whether seropositive mice were also associated with these fine-scale microhabitat types. We therefore employed hierarchical clustering to classify sampling stations into three major clusters according to five of the six vegetation parameters used above to classify degradation level, and each cluster could be defined by specific dominant vegetation characteristics and degradation status ( Figure 4 ; Supplemental Text, Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, further analysis of station-level vegetation measurements revealed that each grid was heterogeneous ( Figure 4 ; Figure S1 ). As the data suggested that the distribution of these rodents was associated with fine-scale “microhabitat” characteristics ( Table S3 ) [ 36 ], we were interested in whether seropositive mice were also associated with these fine-scale microhabitat types. We therefore employed hierarchical clustering to classify sampling stations into three major clusters according to five of the six vegetation parameters used above to classify degradation level, and each cluster could be defined by specific dominant vegetation characteristics and degradation status ( Figure 4 ; Supplemental Text, Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…One plausible biological explanation for the dilution effect with respect to hantavirus transmission is that increased species diversity reduces intraspecific contact among reservoir species, potentially due to behavioral changes which arise from interspecific interactions [ 3 , 65 ]. We previously demonstrated that A. montensis , O. nigripes , and the potential spillover species ( H. megacephalus ) have similar habitat preferences [ 34 ] but tend to avoid other species on small spatial scales [ 36 ]. More importantly, fine-scale conspecific associations were detected independently of habitat; thus, the opportunity for intraspecific transmission is similar across all habitats [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations